친지의 사회적지원, 부부특성, 어머니의 양육특성이 영아발달에 미치는 영향 - 임현주(Hyun Ju Lim); 최항준(Hang Jun Choi); 최선녀(Seon Nyeo Choi) (Korean Journal of child studies, 2012)
The purpose of this study was to investigate the influences of various factors, the social support of friends and relatives, couple's characteristics, and the mother's parenting characteristics, and their impact upon infant development. For the purposes of this study, data was taken from 2078 infants who were born in 2008 and their mothers who participated in the 1st Korean Children Panel Survey of the Child-Care Policy Research Institute. The data collected were processed statistically by means of a structural model and the fit of the model was also found to be very good. The findings indicated that the social support of friends and relatives and couple's characteristics did indeed impact upon an infant's development, with the mother's parenting characteristics having a mediating effect. The direct effect of the social support of friends and relatives on infant development was positive and the results of the effect were the same even when taking into account the mediating effects of the mother's parenting characteristics. The direct effect of a couple's characteristics on the mother's parenting characteristics was negative but the result of it was also positive when taken in conjunction with the mediating effects of the mother's parenting characteristics.